COGNITIVE LEVEL PROFILE AT THE TENTH GRADE OF SENIOR HIGH SCHOOL STUDENTS IN MATHEMATICS PROBLEM SOLVING ON THREE VARIABLES OF LINEAR EQUATION SYSTEM - Khisna - Yumniyati; Imam - Sujadi; Diari - Indriati (Informascope, 2019)
Problem solving is significant skill in facing 21st century. Students have different levels of problem solving. The levels that explain individual abilities in solving mathematics problems are called as cognitive level. It consists of three levels; cognition, metacognition, and epistemic cognition. The cognitive level influences individual in understanding the problem and deciding the right strategies to solve it. The material used to obtain the data is three variables linear equation system, by involving two high ability students at the tenth grade from one of the state senior high schools in Pati. This research employs qualitative method, which the data are collected through task-based interview and time triangulation is applied to validate the data. The results reveal that at the cognition level, students with high ability have an understanding related to conceptual and procedural knowledge, but the ability of students in factual knowledge is low, especially in terminology skill; at the metacognition level, the students are able to write down each strategy in each method, but it is not detail; while at the epistemic cognition level, they are able to explain the weaknesses of a method, but they have not been able to provide a solution  to overcome its weaknesses.